paciente adulto con insuficiencia renal cronica (irc) de causa hipertensiva. - Castro, Maria Jose (2018)
In this clinical case it is intended to report on chronic renal failure of hypertensive cause since the main causes with diabetes cerebrovascular disease, vascular and ischemic nephropathies the age of patients progressively increases and in the first dialysis, they have on average more than 60 years. Early detection, quantification and monitoring of renal functional deficit are based, in practice, on a correct interpretation of creatininemia. When the glomerular filtration rate decreases more than 50%, it is necessary to actively treat the patient: take all necessary measures to try to reduce the rate of degradation of the renal failure of the affected organ. The techniques of treatment of end-stage renal failure are hemodialysis, peritoneal dialysis and renal transplantation. The main glomerular manifestations are proteinuria and hematuria may be accompanied by hypertension and / or renal failure. The predominance of one of these signs and their evolutionary aspect allow to describe different clinical pictures. In most cases, the existence of family history or manifestations results in immunological tests and renal biopsy, allow detecting a specific cause.